Slovenian Pulse 4/2014 - Makarovič, Matej; Rončević, Borut; Tomšič, Matevž; Suklan, Jana; Golob, Tea; Podgornik, Nevenka (Arhiv druzboslovnih podatkov, 2013)
V okviru sklopa vprašanj o blaginji v Sloveniji se je ugotavljalo, kako prebivalci Slovenije doživljajo trenutne gospodarske razmere: kako vidijo svoj materialni standard, kako živijo sami in kako se v Sloveniji na splošno živi, smo napredovali ali nazadovali in kaj naj bi prinesla prihodnost. Anketa se dotika tudi tematike sedanje vlade in ugotavlja, kolikšna je podpora trenutni vladi ter katero stranko bi prebivalci volili, če bi bile parlamentarne volitve ta teden. Anketiranci so podali tudi svoje mnenje o referendumu o arhivih, evropskih volitvah in predlogih za rešitev trenutne politične situacije. The set of questions about the welfare in Slovenia was used to establish how inhabitants of Slovenia experience the economic situation at that time: how they perceive their material standard, how they live alone and how people in Slovenia live in general, if the situation had improved or worsened, and what the future might bring in their opinion. The survey also touched on the topics of the government at that time, establishes the support of the government and which political party inhabitants would vote for in the case of the elections being held the following week. The respondents shared their opinion on the referendum about the archives, on European elections and on proposals to solve the political situation. The set of questions about the welfare in Slovenia was used to establish how inhabitants of Slovenia experience the economic situation at that time: how they perceive their material standard, how they live alone and how people in Slovenia live in general, if the situation had improved or worsened, and what the future might bring in their opinion. The survey also touched on the topics of the government at that time, establishes the support of the government and which political party inhabitants would vote for in the case of the elections being held the following week. The respondents shared their opinion on the referendum about the archives, on European elections and on proposals to solve the political ...